Interaksi Antara Penggunaan Lagu Dalam Konten Digital dan Perlindungan Hak Cipta: Tinjauan Terhadap Undang-Undang Hak Cipta Di Indonesia - Monica Wijaya; R. Rahaditya (Dinasti Research, 2024)
Although copyright laws have provided a framework for protecting musical works, advancements in technology that facilitate access to and distribution of music also create new risks related to copyright infringement. The existing challenges, coupled with the suboptimal regulatory environment, highlight the need for efforts to enhance the protection of song copyrights in digital content. This research aims to analyze the legal protection mechanisms against copyright infringement of songs that occur in the use of digital content. The methodology employed is normative legal research with a legislative approach, utilizing primary data from applicable regulations and secondary data from relevant legal literature. Through qualitative analysis, this study seeks to provide a deeper understanding of how the law protects copyright and how the government addresses the challenges arising in the digital era concerning artistic works in Indonesia. With this understanding, it is hoped that more effective measures can be identified to protect copyright and promote compliance with existing regulations in the music industry.